Tofacitinib Use in Adults with Chronic Inflammatory Disease During the Severe Acute Respiratory Syndrome Coronavirus 2 Pandemic: What Is Known So Far? - Samantha Howland, MPharm; J. Jasper Deuring, PhD; Xiaofeng Zhou, PhD; Yan Chen, MD, PhD; Licia MH Mota, MD; Ryan C. Ungaro, MD, MS (Elsevier, 2021)
ABSTRACT: Background: Concerns have been raised that the risk of severe acute respiratory syndrome coronavirus 2 infection, or more severe or critical coronavirus disease 2019 (COVID-19), may be higher in immunocompromised individuals receiving immunomodulatory therapies compared with immunocompetent individuals. Tofacitinib is an oral Janus kinase inhibitor for the treatment of rheumatoid arthritis, psoriatic arthritis, ulcerative colitis, and polyarticular course juvenile idiopathic arthritis. To date, data on tofacitinib treatment during the COVID-19 pandemic are limited. Objectives: To summarize current understanding of the use of tofacitinib in adults during the COVID-19 pandemic, and discuss research questions that are yet to be addressed, to further inform the safe and effective use of tofacitinib in clinical practice. Methods: We conducted a review of the literature (as of February 2021), to summarize the expert recommendations for the management of rheumatoid arthritis, psoriatic arthritis, and ulcerative colitis in the context of COVID-19, and to assess the current data regarding the use of tofacitinib in adult patients during the pandemic. Results: Current recommendations for rheumatoid arthritis, psoriatic arthritis, and ulcerative colitis state that tofacitinib treatment should be continued during the pandemic, except in cases of positive or presumed severe acute respiratory syndrome coronavirus 2 infection. However, limited data are available; analyses of data from international rheumatology and gastroenterology registries have suggested that tofacitinib may not be associated with an increased risk of hospitalization or treatment switching in adults with COVID-19. Conclusions: Further assessment of tofacitinib use in patients with rheumatoid arthritis, psoriatic arthritis, or ulcerative colitis will be required to elucidate and establish the benefit:risk profile of tofacitinib during the current COVID-19 pandemic.